Supply chain management practices and firms' operational performance - Truong, HQ (2018)
Purpose: the purpose of this paper is to provide an empirical evidence about the relationship between practices of supply chain management (SCM) and operational performance (OP). Design/methodology/approach: based on a comprehensive literature review, a set of SCM practices has been identified and selected to develop a conceptual model as well as to establish their relationship to companies’ OP. The measurement scales of the practices were developed in four steps: identification and development of initial instrument; personal interviews and Q-sort; large-scale data collection; and large-scale analysis in order to ensure unidimensionality, reliability and validity. Structural equation modeling was used to validate the model with the data were collected in Vietnamese garment enterprises. Findings: the study consolidated relationships between the SCM practices and OP. According to the research results, these practices have a “resonant” influence on OP that can explain 52.6 percent variance of this output concept. In particular, customer focus and supplier management both direct and indirect impact on OP while top management support and process control/improvement only have indirect and direct influences on OP, respectively. Research limitations/implications: there are some limitations that can guide academics to new lines of future research: to extend the scope of the survey to include different countries and new situations, so results can be generalized; to consider the impacts of the SCM practices on the entire supply chain performance; and to explore additional factors that can further explain OP, such as operational environment, capital, technology, human resource, etc. Practical implications: the authors suggest that the SCM practices should be implemented as an integrated system rather than independent practices, in which they interact with each other and improve OP. Originality/value: the empirical results of this study provide an evidence to consider the SCM practices as reliable predictors for OP. According to the research, these practices interact with each other and have both direct and indirect effects on OP. In other words, through the mutual interaction among the SCM practices, they have the “resonant” influence on improving OP. Moreover, the proposed research model analyzing the relationship among SCM practices and OP and its validation using the Vietnam garment industry provided valuable insights both from theoretical and practical perspectives.